Using environment-sensitive tetramethylated thiophene-BODIPY fluorophores in DNA probes for studying effector-induced conformational changes of protein-DNA complexes - Šoltysová, Markéta; Güixens-Gallardo, Pedro; Sieglová, Irena; Soldánová, Anna; Krejčiříková, Veronika; Fábry, Milan; Brynda, Jiří; Khoroshyy, Petro; Hocek, Michal; Řezáčová, Pavlína (RSC chemical biology, 2025)
The LutR protein represses the transcription of genes encoding enzymes for the utilization of l-lactate in Bacillus subtilis through binding to a specific DNA region. In this study, we employed oligonucleotide probes modified by viscosity-sensitive tetramethylated thiophene-BODIPY fluorophores to investigate the impact of selected metabolites on the LutR-DNA complex. Our goal was to identify the effector molecule whose binding alters the protein-DNA affinity, thereby enabling gene transcription. The designed DNA probes exhibited distinctive responses to the binding and release of the protein, characterized by significant alterations in fluorescence lifetime. Through this method, we have identified l-lactate as the sole metabolite exerting a substantial modulating effect on the protein-DNA interaction and thus confirmed its role as an effector molecule. Moreover, we showed that our approach was able to follow conformation changes affecting affinity, which were not captured by other methods commonly used to study the protein-DNA interaction, such as electro-mobility shift assays and florescence anisotropy binding studies. This work underlines the potential of environment-sensitive fluorophore-linked nucleotide modifications, i.e. dCTBdp, for studying the dynamics and subtle changes of protein-DNA interactions.